Comparison of media for isolation of poultry intestinal bacteria. - Kelley, R W (1983)
The effects of medium composition, incubation temperature, and length of incubation were determined for recovery of the predominant intestinal bacteria from turkey poults. Incubation of recovery media at 41 degrees C resulted in significantly higher counts than at 37 degrees C. In 2- and 3-week-old turkey poults. RGCAP-30, RGCAP-10, and RGCA-30 gave the highest recoveries of cecal bacteria. M98-5 was less effective and brain heart infusion agar was definitely inadequate. However, there was no significant difference between RGCAP-30 and brain heart infusion agar for recovery of duodenal bacteria. In older birds (6 weeks of age), M98-5 was equal or superior to the RGCA-based media. The choice of a primary isolation medium is thus dependent on the site to be sampled and the age of the bird.